The effect of augmented reality storybooks on the story comprehension and retelling of preschool children - Şimşek, Emine Ela (Frontiers in Psychology, 2024)
This study aimed to compare the retelling and story comprehension performance of two groups of preschool children -an experimental and a control group-who experienced printed and augmented reality storybooks. The participant group consisted of 90 participants, with 45 in the experimental group (22 girls, 23 boys) and 45 in the control group (21 girls, 24 boys). The average age of the children was 54.2 months. In the study, the researcher evaluated children's story-retelling performance using the rubric and used a Story Comprehension Test to measure their story comprehension performance. The researchers utilised the ROAR application to incorporate augmented reality content into the books. In the pre-test phase, the teachers read the designated texts to the children in the experimental and control groups. After the eight-week break, the control group experienced the same texts with printed books, while the experimental group experienced them with augmented reality support. Each child participated individually in the reading process with the teacher. In the study, teachers asked the children to retell the story and asked the questions from the Story Comprehension Test at the end of each book reading section for pre-test and post-test measurements. The pre-test results revealed no significant difference in the two groups' storyretelling and Story Comprehension Test scores. The post-test results indicated a significant difference in the story-retelling performance and Story Comprehension Test scores between the experimental and control groups, favouring the experimental group. Based on these findings, the augmented reality content can potentially enhance children's retelling and story comprehension performances.